Supercritical Fluid Extraction of Fluid Catalytic Cracking Slurry Oil: Bulk Property and Molecular Composition of Narrow Fractions - Li, Weidong; Chen, Yilong; Zhang, Linzhou; Xu, Zhiming; Sun, Xuewen; Zhao, Suoqi; Xu, Chunming (Energy & fuels, 2016)
The supercritical fluid extraction and fractionation (SFEF) method has the capacity of separating heavy petroleum residue into fractions with different processabilities. Different from traditional heavy residue feedstock, slurry oil (SLO) is a heavy liquid product from the fluid catalytic cracking (FCC) process, and there is concern for its potential application in producing carbonaceous materials. The high-value utilization of FCC SLO depends upon the aromatic and contaminate contents in the feedstock. The present study aimed to extend the SFEF method to the FCC SLO system and investigate the property and molecular composition distribution of derived fractions. A FCC SLO was subject to the SFEF process and separated into 13 extract fractions with each 5 wt % yield and 1 unextracted end cut. Systematic bulk property measurements, including boiling point distribution, density, molecular weight, viscosity, and carbon residue, were performed on each fraction. Hydrocarbon molecules in different fractions were characterized in terms of hydrocarbon types and molecular composition by gas chromatography–mass spectrometry (GC–MS) and high-resolution mass spectrometry, respectively. After separation, allof the asphaltenes were removed from extracts. With an increasing extraction pressure, the derived fraction has a growing boiling point, aromaticity, and polarity. Hydrocarbon-type analysis shows that aromatics predominated in the feedstock and most of the fractions. The aromatic content gradually increases with the extracted pressure. The high-resolution MS result shows that SLO is a low-molecular-weight sample with a high aromaticity and short side chain. The measured aromaticity value and GC–MS-measured ring number show a similar increasing trend with the growing extracted pressure. The lower phenanthrene/pyrene ratio indicates that heavier SFEF cuts have potential to have good mesophase development performance.